(untitled) (Fiep Bulletin - online, 2014)
As endurance and flexibility are motor abilities crucial for correct and forehand performance of moves, and having as an aim to get as much information about motor abilities crucial for top performance in jazz – ballet, authors decided to apply the model of aerobic to the training process for jazz – ballet dancers. The aim of the research was to define the effects of applied model, on development of endurance and flexibility, to confirm its positive influence on these abilities with jazz – ballet dancers. The research was carried with 20 female respondents, jazz- ballet dancers at the age of 12-15, who were members of the national team of Bosnia and Herzegovina in modern dances. The set of five tests for evaluating flexibility and two tests for evaluating endurance were conducted with the dancers. By analysing results obtained T- test, it has been established that there were statistically significant positive changes and statistically significant difference in variables for assessment of booth motor abilities positive which show the positive effects of the applied model of training. On this basis, it can be concluded that the model of aerobic applied in jazz – ballet led to improvement of dancers’ endurance and flexibility.